2013
DOI: 10.1021/jf304680j
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution, and Milk Secretion of the Perfluoroalkyl Acids PFBS, PFHxS, PFOS, and PFOA by Dairy Cows Fed Naturally Contaminated Feed

Abstract: The transfer of the perfluoroalkyl acids (PFAAs) perfluorobutanesulfonate (PFBS), perfluorohexanesulfonate (PFHxS), perfluorooctanesulfonate (PFOS), and perfluorooctanoate (PFOA) from feed into tissue and milk of dairy cows was investigated. Holstein cows (n = 6) were fed a PFAA-contaminated feed for 28 days. After the PFAA-feeding period, three cows were slaughtered while the others were fed PFAA-free feed for another 21 days (depuration period). For PFAA analysis plasma, liver, kidney, and muscle tissue, uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 50 publications
10
92
1
12
Order By: Relevance
“…Angus cattle was a fast excreter for PFOA, with a 1 mg/kg bw dose being totally excreted (urine) within nine days [203], but not for PFOS, for which about one third of the dose (8 mg/kg bw ) was still present in the plasma after 28 days, thus becoming a potential exposure source for carnivorous humans [204]. Greatly different kinetics for PFOS and PFHxS versus PFOA and PFBA were confirmed in cows fed with contaminated feed [157]. PFOS serum half-life was 1-2 months in mice and rats, ~4 months in cynamolgus monkeys; liver/serum distribution ratios were different [205].…”
Section: Animal (Including Human) Data Show Widely Different Pharmacomentioning
confidence: 94%
See 1 more Smart Citation
“…Angus cattle was a fast excreter for PFOA, with a 1 mg/kg bw dose being totally excreted (urine) within nine days [203], but not for PFOS, for which about one third of the dose (8 mg/kg bw ) was still present in the plasma after 28 days, thus becoming a potential exposure source for carnivorous humans [204]. Greatly different kinetics for PFOS and PFHxS versus PFOA and PFBA were confirmed in cows fed with contaminated feed [157]. PFOS serum half-life was 1-2 months in mice and rats, ~4 months in cynamolgus monkeys; liver/serum distribution ratios were different [205].…”
Section: Animal (Including Human) Data Show Widely Different Pharmacomentioning
confidence: 94%
“…PFOA serum levels can then increase significantly with on-going drinking water exposure [26]. Cows, and hence, dairy milk are not sheltered against PFAS pollution [156,157].…”
Section: Human Exposurementioning
confidence: 99%
“…Accounting for the modeled animal exposure (ng kg À1 bw d À1 ) via water, forages, and top soil, the correspondent concentration in edible tissues (muscle, liver, milk) was derived from animal toxicokinetics data of feeding trials with contaminated grass silage and hay reported in sheep and cow by Kowalczyk et al (2012Kowalczyk et al ( , 2013, and from the observational study in dairy cows by Vestergren et al (2013). Carry-over rates (COR), as ratio between the total amount of PFOS in the tissue/milk of the considered farmed species and the total amount ingested by the animal were derived from the sheep study for liver (9.1), and muscle (11.6).…”
Section: Carry-over Ratesmentioning
confidence: 99%
“…Perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) are the two most frequently detected chemicals in blood and milk in the general population [10]. Because of their long elimination half-lives in humans (3.8 years for PFOA, 5.4 years for PFOS) [11], exploring the pathways of human exposure to these two compounds is necessary.…”
Section: Introductionmentioning
confidence: 99%